1998
DOI: 10.1165/ajrcmb.19.1.3001
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Macrophage Colony-stimulating Factor Augments ICAM-1 and VCAM-1 Activation of Eosinophil Function

Abstract: Intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) are members of the immunoglobulin superfamily adhesion molecules on vascular endothelium and important in the development of eosinophil (EOS) accumulation in allergic inflammation. To define the role of these adhesion proteins in EOS inflammation, peripheral blood EOS from allergic donors were incubated in either buffer (control)-, recombinant human (rh)-VCAM-1-, or rh-ICAM-1-coated plates, and the effects of these adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 60 publications
6
70
0
1
Order By: Relevance
“…4b). The ability to induce eosinophil spontaneous adhesion is more potent with VCAM-1 than with ICAM-1 [28]. From this point of view, the current results demonstrated that the IFN-b-augmented adhesion of eosinophils to HUVECs was still observed following treatment with anti-b 2 integrin mAb.…”
Section: Ifn-b and Eosinophil-endothelial Cell Adhesionsupporting
confidence: 58%
“…4b). The ability to induce eosinophil spontaneous adhesion is more potent with VCAM-1 than with ICAM-1 [28]. From this point of view, the current results demonstrated that the IFN-b-augmented adhesion of eosinophils to HUVECs was still observed following treatment with anti-b 2 integrin mAb.…”
Section: Ifn-b and Eosinophil-endothelial Cell Adhesionsupporting
confidence: 58%
“…1C). Chimeric CYBB mice received either eosinophils from BAL of OVAchallenged CD45.1 mice or eosinophils from the blood of IL-5 transgenic mice, since eosinophils from BAL can differ from blood eosinophils with regard to adhesion molecule expression and cell function (26,44,45). Eosinophils were isolated from the BAL of OVA-stimulated C57BL/6 mice that were prepared by challenging these mice with OVA 24 h before the OVA challenges in the chimeric mice as indicated in the timeline in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of ICAM-1 for eosinophil functions other than locomotion was suggested in several reports. First, in GM-CSF-activated eosinophils, a blockade of ICAM-1 inhibited release of eosinophil-derived neurotoxin and superoxide production (17,40). Second, adherence of eosinophils to fibronectin, an ICAM-1-ligand, significantly up-regulated the release of cytotoxic mediators such as EDN, EPO, and leukotriene C 4 (4 -6, 15, 16), suggesting that cytokine-induced signaling and signaling from ICAM-1 do interact.…”
Section: Discussionmentioning
confidence: 99%